2017
DOI: 10.1002/etc.3919
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of pyrethroids in large urban rivers to sediment toxicity assessed with benthic invertebrates Chironomus dilutus: A case study in South China

Abstract: The importance of pyrethroids as potential stressors to benthic organisms has gradually become evident in urban creeks; however, the occurrence and toxicity of sediment-associated pyrethroids are rarely studied in large rivers. In this context, 10 sediments from a large urban river (Guangzhou reach of the Pearl River in China) were assessed for pyrethroid occurrence and sediment toxicity to the benthic invertebrate Chironomus dilutus. One half of the sediments exhibited lethality to C. dilutus in a 10-d exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Measured concentrations of l-cyhalothrin were close to, or largely exceeded the proposed sediment quality guideline (Ineris) of 1.05 ng g -1 , and similar to levels causing adverse effects to Chironomus dilutus larvae in sediments from Pearl River tributaries in China (Cheng et al, 2017). Cypermethrin, another pyrethroid for which no guideline could be identified, was measured at the same canal sites at (14.8 and 155 ng g -1 ).…”
Section: A-spahssupporting
confidence: 55%
“…Measured concentrations of l-cyhalothrin were close to, or largely exceeded the proposed sediment quality guideline (Ineris) of 1.05 ng g -1 , and similar to levels causing adverse effects to Chironomus dilutus larvae in sediments from Pearl River tributaries in China (Cheng et al, 2017). Cypermethrin, another pyrethroid for which no guideline could be identified, was measured at the same canal sites at (14.8 and 155 ng g -1 ).…”
Section: A-spahssupporting
confidence: 55%
“…The detection of residential-use pesticides (single analyte concentrations up to 55.6 ng g À1 prodiamine; cumulative concentrations up 71.5 ng g À1 ) in CHAT sediment samples is consistent with their hydrophobic character and resultant tendency to partition to sediment and with the predominantly residential land use and general lack of riparian buffers within the CHAT study reach. Notably, the toxicity of bifenthrin and fipronil sulfone to stream macroinvertebrates is well established (Cheng et al, 2017;Nowell et al, 2016;Rogers et al, 2016;Weston and Lydy, 2014) and both were observed in all downstream CHAT locations at sediment concentrations ranging 287-393 ng g À1 organic carbon (OC) and 16-79 ng g À1 OC, respectively. Multiple exceedances of the bifenthrin Threshold Effect Benchmark (TEB) of 170 ng g À1 OC for Hyalella azteca and the fipronil sulfone TEB of 26 ng g À1 OC for Chironomus species (Nowell et al, 2016) raise concerns for toxic effects to benthic organisms in the CHAT system.…”
Section: Protected-stream Sediment Pesticide Exposuresmentioning
confidence: 99%
“…Sediment toxicities toward the benthic amphipod Hyalella azteca, toward the cladoceran Ceriodaphnia dubia, and toward the midge of the Diptera Chironus dilutus are common tools to survey environmental quality of freshwater sediments. When pesticides are also measured, it allows to identify which toxicant causes the observed impairment [11,38,49,59].…”
Section: Occurrence and Composition Of Various Pyrethroids In Water Ementioning
confidence: 99%
“…Deltamethrin was only detected once in this study but at very high levels from an undetermined source. In Southern China, cypermethrin, cyhalothrin, permethrin, and deltamethrin dominate over other pyrethroids in sediments of the Pearl River; their concentrations may reach notably high values in small creek sediments collected upstream in the river [49]. Cypermethrin and permethrin also dominate in sediments from an urban creek, close to Guangzhou (Southern China, [25,61]).…”
Section: Occurrence and Composition Of Pyrethroids In Sedimentsmentioning
confidence: 99%